Highly sensitive capacitive pressure sensor with elastic metallized sponge. (4th September 2019) - Zhang, Youzhi; Lin, Zhengkang; Huang, Xingping; You, Xiaojun; Ye, Jinhua; Wu, Haibin
Abstract: This paper presents a novel capacitive pressure sensor that is capable of making highly accurate measurements at low pressure. Different from the method that many researchers have successfully used to improve the sensitivity of capacitive sensors by using a micro-structured dielectric layer (such as the micro-structured PDMS film), this paper creatively used an elastic metallized sponge (nickel-plated polyurethane sponge) as the elastic porous electrode of the capacitive sensor, so that it can detect very low pressure (such as a 0.2 g soybean). Compared with the traditional capacitive sensor using an insulative polyurethane sponge as the dielectric, the baseline capacitance of the sensor of the same size can increase by 10 times, and it has a better signal-to-noise ratio. In addition, the sensor has good robustness due to the good mechanical properties of the nickel-plated polyurethane sponge. The fabrication process of the sensor is extremely simple, the cost is low, and it can be made into any planar shape. In this paper, we describe the structure, principle and manufacture of the sensor, and present the application on robotic grasping.